2016
DOI: 10.1159/000443414
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Tempol on Acute Kidney Injury Through PI3K/Akt/Nrf2 Signaling Pathway

Abstract: Background/Aims: Tempol is a protective antioxidant against ischemic injury in many animal models. The molecular mechanisms are not well understood. Nuclear factor erythroid 2-related factor (Nrf2) is a master transcription factor during oxidative stress, which is enhanced by activation of protein kinase C (PKC) pathway. Another factor, tubular epithelial apoptosis, is mediated by activation of phosphoinositide 3-kinase (PI3K)/protein kinase B (PKB, Akt) signaling pathway during renal ischemic injury. We teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 45 publications
(58 reference statements)
4
35
0
Order By: Relevance
“…Previous studies have shown that activation of the Nrf2–Keap1 pathway is a key step in oxidative stress . Activation of Nrf2 plays an important role in antioxidation and anti‐inflammation mechanisms, while ROS are produced in the course of endogenous cellular oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that activation of the Nrf2–Keap1 pathway is a key step in oxidative stress . Activation of Nrf2 plays an important role in antioxidation and anti‐inflammation mechanisms, while ROS are produced in the course of endogenous cellular oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Renal ischemia/reperfusion (I/R) results in considerable alterations in cell function and metabolism and in the structural regularity of the proximal tubule [1-7]. Renal I/R is an important effect of renal dysfunction in renal transplantation, surgical revascularization of the renal artery, partial nephrectomy, and treatment of suprarenal aortic aneurysms [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been proposed to contribute to the progression of AKI, including increased inflammation [5,6] and oxidative stress [7,8].…”
Section: Introductionmentioning
confidence: 99%